Analisis Pemilihan Pesawat Terbang Tanpa Awak Dalam Mendukung Operasi Keamanan Di Laut - Marwanto Marwanto; Budi Darmawan; Manahan Budianto Pandjaitan (Journal of Industrial Engineering & Management Research, 2023)
early detection is a crucial element in maintaining maritime security and preventing various threats at sea. In the context of maritime security operations, the use of unmanned aerial vehicles (UAVs) as a means of supporting early detection has attracted attention due to its ability to carry out extensive and real-time monitoring. However, selecting the right drone requires a systematic and objective approach. Therefore, this study aims to analyze the selection of unmanned aircraft to increase early detection in order to support security operations at sea using the Analytical Hierarchy Process (AHP) method. The AHP method is used to overcome complexity in the decision-making process by taking into account various relevant criteria and sub-criteria. Factors considered include the aircraft's technical capabilities, such as operational range, endurance and speed, as well as the sensor capabilities of the aircraft, including optical, infrared and radar cameras. Security and system reliability aspects are also a major consideration, including communication systems that can ensure fast and secure data transmission. In this study, the AHP-based assessment involved the participation of experts and stakeholders related to security operations at sea. They provide preferences and relative weights of each criterion to determine the priority and importance of each factor in the selection of unmanned aircraft. The results of the analysis show that the selection of suitable unmanned aircraft can increase the efficiency and effectiveness of security operations at sea with an emphasis on early detection. Unmanned aircraft that have superior technical capabilities, sophisticated sensors, and reliable communication systems are a priority in supporting security operations at sea